2010
DOI: 10.1016/j.ssresearch.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic residential segregation and household structure: A research note

Abstract: This study examines how patterns of racial and ethnic segregation in U.S. metropolitan areas vary by household structure. Specifically, using tract-level summary files from the 2000 decennial census, we estimated levels of metropolitan segregation for different racial and ethnic groups by household composition and poverty status. We find that when using the dissimilarity index, white households with children, and especially poor ones, are more segregated from black, Hispanic, and Asian households than are whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 16 publications
1
46
1
Order By: Relevance
“…Thus, SALA households self‐segregate based on their stage in the life cycle, as they require less space than a household with a spouse and children (South and Deane, 1993). Even married‐couple households without children have residential patterns that more closely resemble those of families with children than nonfamily households, suggesting that the former households perhaps either anticipate having children soon or recently had children leave the home (Iceland et al, 2010; Frey and Berube, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, SALA households self‐segregate based on their stage in the life cycle, as they require less space than a household with a spouse and children (South and Deane, 1993). Even married‐couple households without children have residential patterns that more closely resemble those of families with children than nonfamily households, suggesting that the former households perhaps either anticipate having children soon or recently had children leave the home (Iceland et al, 2010; Frey and Berube, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, marriage, or at least the legal registration of a partnership, is required to qualify for such family reformation. Research in the United States has shown that mixed‐nativity households live in a less segregated way than do households in which both heads are foreign born (Iceland & Nelson ). In a similar vein, it could be assumed that households with one foreign‐born head live in a more segregated way than do households without foreign‐born heads.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…None of these theories pay attention to life cycle and household composition characteristics (Iceland, Goyette, Nelson, & Chan, ). However, residential mobility researchers have consistently found that someone's life cycle phase and transitions, and their household composition as a manifestation thereof, are important to understanding residential preferences and decisions (see, e.g., Clark & Dieleman, ; Clark & Onaka, ; Coulter & Scott, ; Marsh & Iceland, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical work on how household organization and type affect segregation is relatively sparse but finds, for example, that families with children are more racially segregated than single-person households (Iceland et al 2010). Thus, changes in the way groups organize into households, such as having relatively more single-person households and fewer families with children, could change levels of segregation.…”
Section: What Drives Changes In Neighborhood Segregation?mentioning
confidence: 99%